2016
DOI: 10.1007/s10517-016-3404-4
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Transduction of Neurons in Adult Brain: Evaluation of Inflammatory Response and Cognitive Effects in Mice

Abstract: We evaluated the effect of hippocampal injection of lentiviral particles p156-CMV-EGFP on behavior, learning, and microglial Iba1(+) cells activation in mice. Testing in the open field and elevated plus-maze revealed higher anxiety levels in lentiviral-injected mice in comparison with animals injected with vehicle. At the same time, lentivirus injection did not change learning and memory of mice in the hippocampal-dependent fear conditioning task. Microglia density in lentivirus-injected mice was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We avoided using this approach because microglia can respond to viral infection (Kunitsyna et al, 2016;Martianova et al, 2019), which may be a confounder in these types of studies. In virusinfected animals, CNO-induced activation of hM3Dq was able to elicit allodynia in male rats (Grace et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We avoided using this approach because microglia can respond to viral infection (Kunitsyna et al, 2016;Martianova et al, 2019), which may be a confounder in these types of studies. In virusinfected animals, CNO-induced activation of hM3Dq was able to elicit allodynia in male rats (Grace et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this study we found that expression of Il1b and Ccl2 are increased in the VTA of mice expressing shMdk, and that Ccl2 expression is increased in the VTA of Mdk −/− mice. One caveat to the lentiviral injections is that the lentivirus could potentially activate glia at the site of injection, causing increased cytokine expression (Kunitsyna et al 2016). Since we found that Ccl2 expression increased in both the Mdk knockout mice and in mice injected with Mdk lentivirus, it is likely that this increase is due to a specific effect of decreased Mdk levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that intra-hippocampal injection of a lentiviral particles (p156-CMV-EGFP, which is a similar construct to ours) with minimum content of transgenes does not change learning and memory of mice in the hippocampal-dependent fear conditioning task (Kunitsyna et al, 2016). Therefore, it is unlikely that GFP expression per se could improve avoidance memory in our study.…”
Section: Discussionmentioning
confidence: 55%